'Les petits bruits': little noises and lower volumes in Catherine Breillat's Romance (1999) and Anatomie de l'enfer (2004). Issue 4 (2nd October 2018) - Talijan, Emilija
Abstract: This article offers a discussion of the role of noise in the work of Catherine Breillat, and evaluates its importance in relation to the pornographic. The author argues that by focusing attention on the auditory, we open up another sensory dimension through which to think about Breillat's key relationship with the pornographic and her appeal to listening in spectatorship. Drawing on the conventions of sound in pornography and discussing how Romance (1999) and Anatomie de l'enfer/Anatomy of Hell (2004) respond to these sounds, the attention to Breillat's sonic practice offered here shows how noise reflects on wider questions of the 'real' and representations of the female body and pleasure that are at stake in Breillat's work more broadly. Attending to the noises of the body, noises emitted by Breillat's female protagonists and to her soundscaping, this article asks what possible critique of the pornographic thinking about noise offers, as well as what forms of resonant intimacy are constructed through Breillat's formal engagement with volumes and amplitudes.